THE HIGH IMPACT OF WORK ETHICS ON EMPLOYEE PERFORMANCE IMPROVEMENT - Shinta Oktafien; Anton Budi Santoso (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of this research is to find out how much influence a high work ethic has on improving employee performance at Balai Penelitian Tanaman Sayuran (BALITSA). The population in this study were employees who worked in this institution with a total sample of 105 respondents and the sampling technique was simple random sampling. As for the research method used in this study, namely in the form of survey research methods with processing techniques and data analysis using simple regression analysis. Based on the results of data processing and analysis, it is known that a high work ethic can have a significant effect on improving employee performance at Balai Penelitian Tanaman Sayuran (BALITSA). Thus, it is concluded that if every employee at work is able to show positive behavior and high morale, then the work results shown by these employees in carrying out their duties and responsibilities can be even better.